IMPLEMENTATION OF OCCUPATIONAL SAFETY AND HEALTH (OSH) IN PREVENTING EMPLOYEE WORK ACCIDENTS AT THE REGIONAL DISASTER MANAGEMENT AGENCY (BPBD) PURWOREJO REGENCY - Hartati, Sri; Nurdin, Ismail; Galeria, Beta (Department of Government, FISIP, Universitas Padjadjaran, 2024)
Occupational Safety and Health (OSH) is an effort to create a safe and healthy work environment and reduce work accidents and work-related diseases, which will have an impact on employee work productivity. This research aims to find out how occupational health and safety (OSH) is implemented to prevent employee accidents at the Regional Disaster Management Agency of Purworejo Regency, the inhibiting factors, and the efforts made to overcome obstacles in implementing OSH. This research uses a qualitative method with an inductive approach. Interviews, observation, and documentation were carried out during data collection, while data analysis was carried out through data reduction, data presentation, and conclusion. The research results show that OSH implementation is relatively good. There are still obstacles, namely weak management control, the OSH management system needing to be implemented, and a lack of employee awareness of the use of Personal Protective Equipment (PPE). Efforts to overcome obstacles were carried out by reintroducing the employee health care program into the 2023 budget, involving department heads in the monitoring process and socializing the use of Personal Protective Equipment.gb777